2007
DOI: 10.1080/17470910701391711
|View full text |Cite
|
Sign up to set email alerts
|

The face of rejection: Rejection sensitivity moderates dorsal anterior cingulate activity to disapproving facial expressions

Abstract: Previous research has examined neural responses to threatening facial expressions such as those displaying anger, fear, and disgust. Here, we examined neural responses to a different type of threatening facial expression that primarily signifies a threat to social connection, namely a "disapproving" facial expression. We hypothesized that neural responses to disapproving facial expressions would be moderated by individual differences in rejection sensitivity. Using functional magnetic resonance imaging (fMRI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 53 publications
(89 reference statements)
6
96
2
Order By: Relevance
“…In both of these studies, participants knew ahead of time that they were going to be asked to reflect on these breakups during the scanning session, so there was nothing unexpected about the task; however, reliving the rejection experience still led to increased activity in the dACC. Likewise, it has also been shown that rejection sensitivity, the tendency to expect to be rejected, was associated with increased dACC activity in response to viewing disapproving facial expressions, cues which signify the possibility of social rejection (Burklund et al 2007). If the dACC were simply sensitive to expectancy violations, we would predict that those who most expect rejection would show less activity in the dACC in response to rejecting cues, but that is not what was observed.…”
Section: Eisenbergercontrasting
confidence: 39%
“…In both of these studies, participants knew ahead of time that they were going to be asked to reflect on these breakups during the scanning session, so there was nothing unexpected about the task; however, reliving the rejection experience still led to increased activity in the dACC. Likewise, it has also been shown that rejection sensitivity, the tendency to expect to be rejected, was associated with increased dACC activity in response to viewing disapproving facial expressions, cues which signify the possibility of social rejection (Burklund et al 2007). If the dACC were simply sensitive to expectancy violations, we would predict that those who most expect rejection would show less activity in the dACC in response to rejecting cues, but that is not what was observed.…”
Section: Eisenbergercontrasting
confidence: 39%
“…1). As noted in the introduction, several areas, including lateral and medial PFC and vACC have been found in previous research on social exclusion (e.g., Burklund, Eisenberger, & Lieberman, 2007;Eisenberger et al, 2003;Fig. 2.…”
Section: Discussionmentioning
confidence: 95%
“…Although initial social exclusion research mainly focused on the dorsal anterior cingulated cortex (dACC), insula, and right ventral lateral prefrontal cortex (RVLPFC; Eisenberger et al, 2003), more recent studies found that other stressrelated regions such as the hypothalamus and regions in the lateral and medial prefrontal cortex (in particular, BA8) were involved in responses to social exclusion as well . In addition, other studies -using the same ball-tossing exclusion paradigm -have found activity in the ventral part of the anterior cingulate cortex (vACC; Burklund, Eisenberger, & Lieberman, 2007;Masten et al, 2009). This latter finding is consistent with results from other studies indicating that the ventral areas of the anterior cingulate cortex are associated with affective responses to social rejection (Bush et al, 2000;Sommerville et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Increased dorsal ACC/mPFC to exclusion may be dependent on individual differences. As dorsal mPFC activity is especially pronounced in individuals sensitive to interpersonal rejection [24], [25], anxiously attached [26], and/or having low self-esteem [27,28]. Therefore, dorsal ACC/mPFC responsivity to social rejection may also be evident in individuals with CEM.…”
Section: Introductionmentioning
confidence: 99%